Usefulness of screening tools in the evaluation of long-term effectiveness of DREZ lesioning in the treatment of neuropathic pain after brachial plexus injury - Haninec, Pavel; Kaiser, Radek; Mencl, Libor; Waldauf, Petr (BMC neurology, 2014)
BACKGROUND: Despite high success rate of DREZ lesioning in the treatment of intractable central pain, there is still a significant incidence of patients without satisfactory post-operative effect. The aim of the study was to evaluate the long-term effect of DREZ lesioning using both a subjective assessment using a visual analog scale (VAS) to quantify residual pain and an assessment using the screening tool (painDETECT Questionnaire, PD-Q). METHODS: DREZ lesioning was performed in 52 patients from a total 441 cases with brachial plexus injury (11.8%) during a 17-year period (1995-2011). The effect of surgery was retrospectively assessed in 48 patients. RESULTS: A decrease in pre-operative pain by more than 75% (Group I) was achieved in 70.8% of patients and another 20.8% reported significant improvement (Group II). The surgery was unsucessful in 8.4% (Group III). We found a significant correlation between 'improvement' groups from both methods of assessments. Patients from Group I usually complained of residual nociceptive pain according to PD-Q, patients from Group II typically had pain of unclear origin, and all cases those in Group III suffered from neuropathic pain, Cramer's V = .66, P < .001. Overall, 66.7% of patients had resolved neuropathic pain, 20.8% patients had more serious complaints and may also suffer from residual neuropathic pain, while 12.5% had unresolved neuropathic pain. CONCLUSION: DREZ lesioning is a safe and effective method with success rates of about 90%. PD-Q scores correspond to subjective satisfaction with the surgery and it seems to be a suitable screening tool for finding patients with residual neuropathic pain after surgery.
Keywords: dospělí; elektrokoagulace; průzkumy a dotazníky; Female; neuralgie; Pain Measurement; Brachial Plexus; Adult; mladý dospělý; ženské pohlaví; Surveys and Questionnaires; Spinal Nerve Roots; lidé; Pain, Intractable; hodnocení výsledků zdravotní péče; Electrocoagulation; míšní kořeny; měření bolesti; plexus brachialis; retrospektivní studie; Male; Aged; Young Adult; Neuralgia; lidé středního věku; senioři; mužské pohlaví; Retrospective Studies; Middle Aged; nezvladatelná bolest; Outcome Assessment, Health Care; Humans